Heterotopy of the hysterical body - Mackiewicz, Wojciech; Barański, Jarosław (Hybris, 2021)
Heterotopia is the space of otherness, a counter-space. A very specific type of heterotopia is a human’s body, especially in its illness and sickness. Hysteria, the disease which can imitate many other diseases, is here a crucial example. From its ancient beginnings until today hysteria makes us reflect on the essence of illness and disease, on the definition of the human condition, on the social role of a healthy and ill human body, etc. The archeology of hysteria explains how disorders shape medical standards.